2020
DOI: 10.15611/pn.2020.6.01
|View full text |Cite
|
Sign up to set email alerts
|

The digital skills conducive to using the Internet and mobile banking services in light of nationwide own research results

Abstract: The digital skills conducive to using the internet and mobile banking services in light of nationwide own research results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The Ministry of Digitization (2020) has prepared the Digital Competence Development Program until 2030 aimed at an ongoing increase in the level of digital competences by providing every Pole with the possibility of their development according to individual needs, which ultimately is supposed to contribute towards building an inclusive, open and modern society, and thus a better quality of life for the citizens. Obviously, through education the state develops general digital skills of its citizens, but as the results of the research conducted by the authors have shown -people with higher general digital skills also have higher skills used in online and mobile banking (Adamek & Solarz, 2020). The latter should be developed by banks, e.g., as part of Corporate Social Responsibility (CSR), which nowadays is extended to include Corporate Digital Responsibility (CDR) (see Lobschat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Digitization (2020) has prepared the Digital Competence Development Program until 2030 aimed at an ongoing increase in the level of digital competences by providing every Pole with the possibility of their development according to individual needs, which ultimately is supposed to contribute towards building an inclusive, open and modern society, and thus a better quality of life for the citizens. Obviously, through education the state develops general digital skills of its citizens, but as the results of the research conducted by the authors have shown -people with higher general digital skills also have higher skills used in online and mobile banking (Adamek & Solarz, 2020). The latter should be developed by banks, e.g., as part of Corporate Social Responsibility (CSR), which nowadays is extended to include Corporate Digital Responsibility (CDR) (see Lobschat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%